PENERAPAN STRATEGI PEMBELAJARAN AKTIF PADA MATA PELAJARAN FIQIH DI MTs MA’ARIF NU I JATILAWANG KABUPATEN BANYUMAS - Saiful Hamdi; Qurotul Aini Farida (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
Learning strategy is an important thing that need to be paid attention, prepared andexecuted by teacher when learning process of fiqih executed. Because active learningstrategies have an effect on the outcomes of the learning itself, the right strategy, thenthe results can be maximized. The results of research conducted by the Researcher is anactive learning strategy used in learning fiqih is a kind of card, ask curious, everyoneis a teacher here, read aloud, index card teachers and jigsaw learning. Download inthe material to be submitted for learning strategies that will be in accordance with thematerial to be submitted. Using an active learning strategy is not an obligation for allteachers of jurisprudence, will this active learning strategy be the creativity of one's ownteacher to facilitate the teaching and at the same time grow the interest for the learnersto get involved in the learning. In practice the use of Active learning strategy is not usedalone, in other words according to the learning material.